Approaches and methods for ecosystem services assessment in the North of Portugal: from supply modeling to land management optimization - Azevedo, João (2018)
In the last decades, ecosystems services (ES) in the North of Portugal have been assessed typically for sets of ES addressed individually based on indicators (e.g., LULC) but also through mechanistic and non-mechanistic modeling (e.g., hydrological modeling, InVEST). Economic evaluation has been applied based mostly on the combination of ES supply in biophysical units with market prices or value attributed by other techniques (e.g., avoided cost, unit value transfer). Such studies, and the approaches and methods involved, have been helpful in demonstrating the magnitude and dynamics of the supply of a series of ES in the region, both in biophysical and monetary units, and to inform regional planning and management of natural resources, such as forests. These studies have been changing the perception of stakeholders regarding forest systems and their management. Despite the importance of ES research conducted so far, there is an ongoing effort to further develop ES assessment in the region, conceptually and methodologically, namely by overcoming some of the intrinsic constraints of the approaches and methods used. Improvements intend to better integrate different ecosystem functions and services, to eliminate double counting, and to address the interactions between supply and demand of ES at several scales. The incorporation of capabilities of land-use and management optimization based on the supply and value of ES is also currently a research goal in the region. Recent developments have been based on operational research tools developed for the forest sector in the region of Bragan ça addressing ecosystem services from heuristics, multi-criteria and linear programming perspectives, expecting to solve complex spatially explicit management alternatives problems based on ES. In this presentation we will introduce these tools and their adjustment and applications in the assessment of ES in the region.